1999
DOI: 10.1111/j.2042-3306.1999.tb05176.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of omeprazole paste in the treatment and prevention of gastric ulcers in horses

Abstract: Summary Equine gastric ulcer syndrome (EGUS) is very common among performance horses, with a reported prevalence of approximately 90% in racehorses, and also >50% in foals. Omeprazole, an acid pump inhibitor 5 times more potent than ranitidine, has been used with great success to treat EGUS. This multicentre study of Thoroughbred racehorses with endoscopically verified gastric ulcers was designed to demonstrate the efficacy of an equine oral paste formulation of omeprazole in the treatment and prevention of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
131
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 16 publications
5
131
2
1
Order By: Relevance
“…Equine gastric ulcer syndrome is present in 70 to 90% of active racehorses [1,15]. Racehorses are usually housed individually in a stall or a small paddock except during training.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Equine gastric ulcer syndrome is present in 70 to 90% of active racehorses [1,15]. Racehorses are usually housed individually in a stall or a small paddock except during training.…”
mentioning
confidence: 99%
“…Horses were restrained with a nasal twitch, and the endoscope (VQ-8303A, Olympus, Tokyo, Japan) was inserted into the stomach through the nose. The severity of gastric ulcer was assessed from score 0 to 3 based on Andrews' 4-grade scoring system [1]. Based on the first endoscopic examination, 23 of 85 (27.1%) horses were identified as having gastric ulcers, and among them 20 (23.5%) and 3 (3.6%) ulcers were scored as 1 or 2, respectively ( Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The bioavailability of oral enteric coated omeprazole is variable but unaffected by feeding or fasting [16]. Withdrawal of omeprazole after 56 days of treatment has been reported as resulting in a rapid return of gastric ulceration [15]. However, another study showed only a 20% recurrence rate following withdrawal of omeprazole following 56days treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…following 25-56 days of treatment [12][13][14][15]. The bioavailability of oral enteric coated omeprazole is variable but unaffected by feeding or fasting [16].…”
Section: Introductionmentioning
confidence: 99%